Case Studies in Financial Decision Making. - Eades, Kenneth; Harrington, Diana R. (Journal of Finance, 1987)
This casebook looks at the world confronting financial managers today. Considering both the domestic and international issues faced by today's companies, the book provides 44 real-life cases, from basic to advanced level.